GAMBARAN TINGKAT KESEGARAN JASMANI LANSIA LAKI-LAKI TIDAK ANEMIA DI DESA DAN KOTA - Rosmalina, Yuniar; Permaesih, Dewi; Moeloek, Dangsina (PERSATUAN AHLI GIZI INDONESIA, 2007)
PHISICAL FITNESS PROFILE OF NON ANEMIC MALE ELDERLY PEOPLE IN RURAL AND URBANBackground: Physical fitness is considered as one indicator of community health status of thecommunity including elderly people. One of the benefit is elderly could live independently and dotheir daily activities without assistant. The study on Physical fitness of non anemic male elderlypeople has been conducted in the rural and the urban area.Method: The data collection including 6 components of physical fitness (gait balance, musclestrength, endurance, body composition, flexibility and memory test), antropometric measurement(body weight, height and mid-arms circumference) and Hemoglobin level.Result: The result shows that 217 elderly in rural and 281 elderly in urban area were participatedon the study. The proportion of age was 42.9 percent in rural was > 70 years and 37.2 percent inurban was 60-64 years old. Based on the physical fitness measurements the proportion of ruralelderly who had low level physical fitness was 57.1 percent and 42.9 percent considered asmoderate level. While in urban area the proportion of elderly who had low level physical fitnesswas 82.6 percent and 17.4 percent considered as moderate level. Out of 6 component of physicalmeasurements body, cardiovascular endurance and body composition has high contribution to thedifferent of physical fitness level between rural and urban.Conclusion: The physical fitness level of non anemic male elderly in rural better compared to theurban.Keywords: elderly, physical fitness, non anemic